Intercollegiate Athletes - Cotrufo, Raymond J. (Sports Leadership: A Concise Reference Guide, 2015)

Applying Intergroup Contact Theory to the Sport Management Classroom - Bruening, Jennifer; Fuller, Rhema D.; Cotrufo, Raymond J.; Madsen, Rachel M.; Evanovich, Justin; Wilson-Hill, Devon E. (Sport Management Education Journal, 2014)
Allport’s (1954) intergroup contact hypothesis states that interactions with members of an out-group, particularly of a different racial and/or ethnic group, are effective in changing attitudes about diversity (Allport, 1954; Pettigrew, 1998). In this study, the intergroup contact hypothesis was applied to the design of a sport management course. The classroom component focused the role of sport in education, health, and leadership development, and the application was structured sport and physical activity programming with school-age children at several urban sites. Data were gathered from 91 college students over 3 years about course-related experiences and how the students’ backgrounds influenced their social identities and understanding of out-group members. Results showed that intergroup contact effectively assisted in developing understanding and cooperation and reducing negative attitudes between groups. The participants received diversity education, via intergroup contact, both inside and outside the classroom, which will potentially equip them to take proactive strategies when managing organizational diversity in the sport industry.
Keywords: dept.rec